Selection as the main direction of scientific studies and main steps of selection and breeding work in Ukraine (a review) - O. Krasnopolska (Ribogospodarsʹka Nauka Ukraïni, 2021)
Objective: For a long time, selection, as a science, has been dealing with the creation of varieties and hybrids of agricultural plants, animal breeds, microorganism strains and studying the methods of all of the above. At the same time, like any component of science, it has its own directions of development, and improves them in time. Therefore, the purpose of this work was to investigate the historical development of selection as a science, to analyze the current state, and to characterize the application of basic breeding methods in aquaculture in Ukraine. Findings: The author of the work reviewed and analyzed professional scientific literature on the development of selection as one of the methods of scientific studies. In particular, the historical aspects of the development of selection in crop production and animal husbandry, including fish farming, have been considered, and its main directions have been highlighted. A promising method for the development of synthetic selection was proposed: reciprocal crossing, and the current state of selection and breeding work in fish farming was described. Practical value: The review of literature sources can be useful for the preparation of lecture material during the training process for training specialists in the specialty 207 "Aquatic Bioresources and Aquaculture", including specialists in ichthyology, veterinary medicine, zoology.